Combustion chemistry of alkenes and alkadienes. (May 2022) - Zhou, Chong-Wen; Farooq, Aamir; Yang, Lijun; Mebel, Alexander M.
Abstract: Alkenes formed, during the refining of crude oil, by cracking the heavier fractions are present in transportation fuels in significant amounts, up to as much as 15–20% in gasoline. Moreover, alkenes are also the major intermediate products of the oxidation of alkanes, which play a significant role in autoignition chemistry. This review has assessed the recent progress in gas-phase detailed kinetic model development for species with C=C double bond, mostly C2–C10 alkenes and 1, 3-butadiene. The compiled knowledge on alkene combustion chemistry enabled a better understanding of the influence of the number and the position of the C=C double bond on the chemical kinetics and hence combustion behavior of alkenes in engines. At first, the article gives an extensive overview of fundamental combustion experiments by considering studies of C2–C10 alkenes and 1, 3-butadiene in shock tubes, rapid compression machines, laminar flames, and jet-stirred and flow reactors. The value of the data from such experiments is critically discussed. Secondly, this article highlights the important reaction classes involved in alkene oxidation over low-, intermediate- and high-temperature ranges. Combustion chemistry covering C2 to C10 alkenes, with a special emphasis on C2 to C7 isomers is discussed by presenting a large body of experimental and modeling investigations. Detailed chemistry differences between alkene isomers and also between alkenes and alkanes are also addressed. Thirdly, the article presents important reaction pathways for PAH precursor formation in different alkenes. Finally, a summary of the distinguishing features of alkene combustion chemistry and an outlook towards future research in this area are presented. This review is focused on linear and branched chain alkenes, and the chemistry of cyclo-alkenes is not included.